High Order Coherence Functions and Spectral Distributions as Given by the Scully-Lamb Quantum Theory of the Laser - Peng, Tao; Zhao, Xingchen; Shih, Yanhua; Scully, Marlan O. (Frontiers in Physics, 2021)
We propose and demonstrate a method for measuring the time evolution of the off-diagonal elements ρ(n,n+k(t)) of the reduced density matrix obtained from the quantum theory of the laser. The decay rates of the off-diagonal matrix element ρ(n,n+k(t)) (k=2,3) are measured for the first time and compared with that of ρ(n,n+1(t)), which corresponds to the linewidth of the laser. The experimental results agree with the Scully-Lamb quantum theory of the laser.